Photoreduction of aliphatic and aromatic thioketals: new access to the reduction of carbonyl groups by a desulfurization chain process - Oksdath Mansilla, Gabriela (2013)
Aromatic and aliphatic ketones can be converted to methylene groups by desulfurization of the corresponding dithioketals in moderate to good yields. The reaction proceeds by photoinduced electron transfer from tert-BuOK in the presence of 1,4-dicyclohexadiene as hydrogen atom donor. The diene is able to trigger and keep a chain process by hydrogen transfer–proton transfer reactions.